Review of The Law of Special Citizenship on Naturalization in Indonesia - Munif Rochmawanto; Syamsul Arifin; Enik Isnaini; Dwiki Wahyu Ramadhan (Jurnal Independent, 2026)
This study presents a legal review of the special citizenship law concerning naturalization in Indonesia, employing a normative juridical research method. The research approach includes statutory analysis, conceptual analysis, and comparative legal analysis, utilizing primary legal materials such as Law No. 12 of 2006 on Citizenship of the Republic of Indonesia, as well as secondary legal materials including academic texts and legal doctrines. The analysis examines two primary naturalization pathways: ordinary naturalization and special naturalization. Special naturalization is granted to foreigners who have rendered exceptional services to the Indonesian nation or who possess high expertise beneficial to national development. This study explores the legal criteria, procedural distinctions, and discretionary authority vested in the executive branch in granting special citizenship through a qualitative normative analysis. Furthermore, it identifies legal ambiguities, inconsistencies in implementation, and potential conflicts with constitutional principles of non-discrimination and legal certainty. The findings indicate that while special naturalization serves as an instrument to attract talent and reward extraordinary contributions, its application lacks transparent guidelines, leading to potential arbitrariness from a legal perspective. This review recommends the formulation of clearer objective criteria and judicial oversight mechanisms to align special naturalization practices with the rule of law and principles of good governance.